Analysis of the "No Poverty" Sustainable Development Goals in West Nusa Tenggara - Nurul Maulidyan; Ida Nuraini (BASKARA : Journal of Business and Entrepreneurship, 2026)
One of Indonesia's sustainable development goals (SDGs) is to eliminate poverty by 2030. In March 2022, the number of poor people in West Nusa Tenggara was 13.95%, or 8th out of all provinces in Indonesia. The purpose of this study is to determine the variables that affect poverty in West Nusa Tenggara. The research objects are 10 regencies and cities in West Nusa Tenggara. The data used is secondary data from 2018-2022 obtained from the Central Bureau of Statistics. With the panel data regression analysis tool, the results show that the GRDP variable has a significant positive effect on poverty, the labor force participation rate variable has a significant negative effect on poverty, while the average years of schooling and per capita expenditure variables do not affect poverty in West Nusa Tenggara